Gregório de Matos: do barroco à antropofagia - Lima, Samuel Anderson de Oliveira (2013)
The exponential figure of Gregório de Matos e Guerra has been subject of many theoretical discussions through the years, since his apparition in a public place, in the 19th century, and even more, during the 20th century, when he was salvaged by the modernist vanguard. As a result, there are yet two antagonist points of view linked to Gregório de Matos, on one side, there some researchers who defend him, on the other, some of them attack him. The first ones say this poet from Bahia was the first literary voice in Brazil, from the Baroque basis, while the last ones say he is a merely plagiarist of the Spanish poets from the 17th century, without a real contribution to the development of Brazilian Literature. With this in mind, this thesis follows the perspective this poet is an anthropophagus-baroque, devouring cultures, with an active participation in the process of our cultural and literary identity. For that reason, it was made a literature review about the biography of this poet trying to break romantic descriptions, emphasizing some scientific facts that can contribute to present the baroque profile of this poet. In this sense, it was discussed the History of Literature focused on this creole poet, mainly based on the historians point of view about the Gregorian poetry in the formation of Brazilian Literature scenery. In the defense of the hypothesis that Gregório de Matos was our first anthropophagus, this work aims to analyze how his poetry reveals the intrinsic characteristics of Baroque and Anthropophagy, focusing its carnivalesque aspect, showing to the world, with a satiric tone, the idiosyncrasies of human life. In this way, analyzing this corpus in Spanish is the strength of this thesis because, besides it is previously unpublished, it contributes to the comprehension of the anthropophagy as a theoretical mechanism that explains the process of formation of our cultural literary identity. Then, we have Augusto de Campos (1968; 1978; 1984; 1986; 1988), Haroldo de Campos (1976; 2010a; 2010b; 2011), Severo Sarduy ([1988?]), Oswald de Andrade (1945; 1978; 2006), Mikhail Bakhtin (2010), Octavio Paz (1979), Segismundo Spina (1980; 1995; 2008), Afrânio Coutinho (1986a; 1986b; 1994), Affonso Ávila (1994; 1997; 2004; 2008), among others, to constitute this theoretical scenery. The Gregorian poetry, in this way, have contributed to the formation of baroque-anthropophagic scenery in Brazilian boundaries, with a special attention to the transition of time, because he is not only from the 17th century, established by the historiography, but his work is present nowadays due to the contemporaneously of his themes, centered to the eternal doubts of baroque man